(An) Endeavor in Receptor Design for Solid State Recognition of Anions/Hydrated Anions - Hoque, Md. Najbul (My University, 2015)
The contents of this thesis entitled “An Endeavor in Receptor Design for Solid State Recognition of Anions/Hydrated Anions” have been divided into seven chapters based on the results of experimental work carried out during the research period. Chapter 1: Introduction This chapter provides a brief introduction on ‘supramolecular host-guest chemistry’ of ionic species with special reference to recognition of anions or hydrated anions. Supramolecular chemistry offer many possible avenues like recognition, catalysis and transport. Anions are ubiquitous in nature. Hence, molecular recognition of anionic species has attracted great interest during the last decades because of the imperative role in various biological and environmental processes. Extensive research effort has been expended toward understanding how host structure influences anion binding with the goal of discovering more effective and more selective anion receptors. A very large number of artificial systems for recognition and sensing of anions have been designed and synthesized by properly exploiting supramolecular concepts. One successful approach for preparing anion hosts has been to synthesize molecules that offer an array of H-bonding sites to the guest. Because H-bonds exhibit directionality, it should be possible to achieve a structure-based recognition for anions of particular shape and size. The binding of anion guests within preorganized macrocyclic systems is relatively more predicated easy to understand supramolecular association but the binding processes of acyclic receptors is unpredictable and very tough to control due to freedom of many conformation. Hence it is great challenge to study receptor-anion assembly of flexible acyclic receptor. Sometimes specially design acyclic receptor forms capsular assemblies which have shown a number of interesting properties e.g. encapsulation of anion/anion–water clusters, capturing aerial CO2 as carbonate, selective salt extraction and anion transportation. On the other hand, Understanding the hydration of anions at the molecular level is thus important as the surface speciation and reactivity of aerosols, which play a key role in atmospheric and oceanic chemical cycles. The characterization of an isolated solvated ion serves to add to information about the solvation properties. As the properties of hydrated ions are quite different from those of isolated ions (in the gas phase) or ions in nonpolar media and are governed by the nature of the surrounding hydration network.
Das, Gopal
Keywords: CHEMISTRY